The correlation between midwives’ support and accessed to Voluntary Counseling and Testing (VCT) on pregnant women - Elfa Rahmawati Fitri; Herlin Fitriana Kurniawati (Universitas Aisyiyah Yogyakarta, 2018)
HIV/AIDS cases in Indonesia are still high including the infection from mothers to the babies. Infection cases from mothers to babies in Yogyakarta Special Province is also found on babies. The preliminary study also obtained the result that in 2015 not all of the pregnant women who were willing to have VCT (Voluntary Counseling and Testing) in Sleman Regency working area. The data of VCT in Prambanan Primary Health Center also shows that the prevalence rate of VCT check as a preventive effort was still low. The research is aimed at investigating the correlation between midwife’s support and VCT on pregnant women in Prambanan Primary Health Center in 2016. The study employed observational analytic with a cross-sectional approach. The population of the study was all mothers who did pregnancy examination and got counseling VCT service. The samples used accidental sampling technique. Data analysis used chi-square with the trustworthy rate 95%. The result of the study showed that there was no correlation between midwife and VCT on pregnant women. It can happen because of the midwife as a professional attendant could not attend the pregnant women full time. It can be concluded that there was no correlation between midwife’s support and VCT on pregnant women in Prambanan Primary Health Center in 2016. It is expected that midwives can identify the problem in VCT on pregnant women by giving emotional and respect support to the patients as well as the families.